2020
DOI: 10.3390/antiox9070571
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Oxidative Stress, Inflammation, and Muscle Damage Markers Following Diet and Beetroot Juice Supplementation in Elite Fencers

Abstract: The aim of this study was to assess the impact of diet and active substances in beetroot juice on the parameters of oxidative stress, inflammation, and muscle damage as well as on the maximum rate of oxygen uptake (VO2max) in elite fencers (10 women, 10 men). Athletes during four weeks realized dietary recommendations (ID) and, after that, diet with freeze-dried beetroot juice supplementation (ID&BEET). At baseline and after each stage, fasting antioxidants, biomarkers of oxidative stress, inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 93 publications
0
38
0
Order By: Relevance
“…The authors of a previous study speculated that beetroot juice consumption might have increased physical activity, ultimately increasing oxidative stress. Additionally, a significant increase in VO 2max was observed after ingestion of beetroot juice without attenuated muscle damage markers, such as CK and LDH [ 68 ].…”
Section: Beetroot Juicementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a previous study speculated that beetroot juice consumption might have increased physical activity, ultimately increasing oxidative stress. Additionally, a significant increase in VO 2max was observed after ingestion of beetroot juice without attenuated muscle damage markers, such as CK and LDH [ 68 ].…”
Section: Beetroot Juicementioning
confidence: 99%
“…One parallel study showed no effect on oxidative stress [ 63 ], whereas one crossover study showed that beetroot juice increased oxidative stress [ 68 ]. Previous studies demonstrated that beetroot juice had no effect on inflammatory responses (IL-6, IL-8, CRP, and TNF-α) following exercise modalities (sprint, plyometric, intermittent, and endurance exercise) regardless of parallel [ 61 , 62 , 63 , 64 ] or crossover [ 67 , 68 ] study design. From these results, it is thought that the antioxidant and anti-inflammatory effects of beetroot juice after exercise may be minimal based on the blood indices.…”
Section: Beetroot Juicementioning
confidence: 99%
“…In vitro [40], it was observed that a shot of BJ manages to supply a large number of bioaccessible antioxidants in gastric and duodenal cells, hypothesizing that this would be an interesting strategy to increase the body's antioxidant status. Some authors showed, in a study with diet control over four weeks of BJ [41], an increase in lipid peroxidation, indicating a change in oxidative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Kozlowska et al stated that the chronic BR consumption enhances lipid peroxidation, and improvement of VO 2max after the BR supplement consumption seems to be dependent on baseline lactic acid dehydrogenase (LDH) activity, and also, on the serum concentrations of malondialdehyde (MDA) and β-carotene. It is suggested that alterations in the ergogenic effect of BR are negatively dependent to alter in serum concentration of MDA, β-carotene, and the activity of LDH ( 57 ). Singh et al stated that the BR ingestion significantly declined the stress markers of plasma hydroperoxides and improves the antioxidant status ( 40 ).…”
Section: Antioxidant Effects Of the Br Supplementationmentioning
confidence: 99%